Math achievement, stereotypes, and math self-concepts among elementary-school students in Singapore. (October 2015) - Cvencek, Dario; Kapur, Manu; Meltzoff, Andrew N.
Abstract: Singaporean elementary-school students ( N = 299) completed Child Implicit Association Tests (Child IAT) as well as explicit measures of gender identity, math–gender stereotypes, and math self-concepts. Students also completed a standardized math achievement test. Three new findings emerged. First, implicit, but not explicit, math self-concepts ( math = me ) were positively related to math achievement on a standardized test. Second, as expected, stronger math–gender stereotypes ( math = boys ) significantly correlated with stronger math self-concepts for boys and weaker math self-concepts for girls, on both implicit and explicit measures. Third, implicit math–gender stereotypes were significantly related to math achievement. These findings show that non-academic factors such as implicit math self-concepts and stereotypes are linked to students' actual math achievement. The findings suggest that measuring individual differences in non-academic factors may be a useful tool for educators in assessing students' academic outcomes. Graphical abstract: Results for implicit (A) and explicit (B) measures of three constructs in elementary-school Singaporean children. Error bars = ±1 SE . N = 267. Asterisks indicate significant differences between boys and girls. *** = p < .00001, ** = p < .0001, * = p < .01. Coefficients at the top of each construct are correlations ( r s) with standardized math achievement. Highlights: Assessed implicit and explicit math–gender stereotypes and math self-concepts. Examined their relationship to standardized math achievement in Singapore. Implicit—but not explicit—math self-concepts were related to math achievement. Implicit—but not explicit—math–gender stereotypes were related to math achievement. Non-academic factors are related to math achievement in a high-achieving culture.